Penggunaan Tablet Tambah Darah dan Upaya Pencegahan Anemia pada Remaja - Sofya, Sri Winarni; Kresnapati, I Nyoman Bagus Aji; Pratiwi, Baiq Yulia Hasni; Qomaliyah, Eka Nurul; Indriani, Nurul; Muhsin, Lalu Busyairi (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
This service aims to introduce the importance of using Blood Supplement Tablets for young women, the impact of anemia in daily life, and knowing foods and drinks that can absorb and inhibit iron intake, so they know how to prevent anemia as early as possible. The method used in this service is participatory, followed by preparation, then counseling, followed by question and answer between the presenter and the audience. The media used in this service are PowerPoint and posters. The results obtained from the counseling were in the form of an increase in the level of knowledge of MAN 3 Mataram students and students regarding the correct use of blood supplement tablets, both for prevention and therapy, and during the outreach the participants were very active in asking questions and answers with the presenters. It is hoped that this increase in knowledge can improve the health status of teenagers in Indonesia, and reduce the rate of anemia and the risk of bleeding during childbirth.